Ser discípulos num tempo de mudança - Cescon, Everaldo (Revista eclesiástica brasileira, 2007)
To prevent the present crisis from becoming structural, the rapid changes of our time demand answers from the Christians, in the light of the Gospel. But how to respond to all this? Which tasks are expected from Christians? The author summarizes the challenges faced by Christians in the early years of the 21st century. He attempts to describe Jesus Christ’s disciple. And finally, he lists a series of possible tasks to be carried out by us, as faithful disciples of Jesus Christ, in order to face those challenges.